THE MECHANISM OF ACID MINE DRAINAGE NEUTRALIZATION WITH LIMESTONE MATERIAL A CASE STUDY AT SETTLING POND 13 OF ASAM-ASAM COAL MINE PROJECT PT ARUTMIN INDONESIA SOUTH KALIMANTAN PROVINCE - ARIFWATI (NIM : 22115302), YUNI
Limestone composed of calsium carbonate compounds (CaCO3) is a type of acid mine drainage (AMD) neutralizer that is often used in sediment ponds. Many factors can affect the effluent quality of an AMD processing system. This research aims to know the form of mechanism that can influence the process of acid neutralization using Limestone, case study on Settling Pond 13 Acid Coal Mine Project PT Arutmin Indonesia. The research method used is to create a theoretical simulation of both modeling using PHREEQC and numerical calculation to simulate various options of neutralizing mechanism. The results showed that the mechanism of acid neutralization of mine acid was influenced by several factors: the quality of the neutralizing agent, the dosage, the dosage limit of saturation index, dissolution process of neutralizing agent, dosing duration interval and the residence time. Based on PHREEQC modelling and theoretical calculation approach, the problem of 60% effluent acidity data are still under pH 6 can be solved by changing the time interval of neutralizing material injection from 60 minutes to 13 minutes to fulfill the need of neutralization time; Dissolution process of limestone before the neutralization process can reduce the need for residence time for 196 seconds; The largest dose of limestone that can be used at SP 13 in order to avoiding oversaturated condition due exceeding the saturation index value limit is 0.21 gr/L; The baffle creation in compartment 3 and 4 can serves as an excavator holder during pool maintenance and also to giving a longer time, so treatment compartment able to provide longer neutralization time; Replacement of neutralizing agent into Lime (CaO) can increase acidity of > 8 and also the time to dissolve the lime requires only Ã‚Â± 2 seconds, 98 % more reactive compare to Limestone.